Green Nail Syndrome, A Rare Infection of Pseudomonas aeruginosa in The Nail - Erike A. Suwarsono (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2020)
ObjectiveA nail infection is a common case caused by fungal infection, thus can make any bacterial correlated infection in the nail can be under-diagnosed. However, Pseudomonas aeruginosa can cause nail infection known as green nail syndrome (chromonychia). Method A 3 years old girl presented with greenish discoloration on the nail plate of the right toenail since previous a month. She came from well-educated family, but the water resource at their home was not good enough. The specimen of nail scraping was sent to the microbiology laboratory. The Gram from nail scraping didn’t show any significant result. After 24 hours, a greenish colony, non-lactose fermenter on the Mac Conkey and a dominant blue-green color colony on the blood sheep agar had grown. The colonies are beta hemolytic, flat and spreading. They were also positive to oxidase and catalase. Result The Gram result from the colony was showed as basil negative Gram. Identification from Vitex 2® concluded as Pseudomonas aeruginosa that resistant to all penicillin derivate and 2nd generation of cephalosporin. However the isolate was still sensitive to ceftazidime, carbapenems, quinolones and amino-glycosides. The treatment was decided using topical fluoroquinolone nadifloxacin, and gave a significant result in a month Conclusion Green nail syndrome that is caused by P. aeruginosa infection could be treated by topical fluoroquinolone for 1-2 months